Integrating Creative Economy in the National Sustainable Development Plan - Susanti, Rina; Silvia, Engla Desnim (Pascasarjana STIE Amkop Makassar, 2024)
This research explores the integration of the creative economy into sustainable national development, focusing on its potential and challenges. The study highlights key sectors such as design, digital technology, tourism, and the arts, which contribute to economic growth, innovation, and cultural sustainability. However, it also identifies significant obstacles, including inadequate policy support, unequal access to markets, and the need for a skilled workforce. Through qualitative methods, including in-depth interviews and policy document analysis, the research examines the role of government in fostering a thriving creative economy. Case studies from countries like Sweden and Finland, which have successfully integrated creative industries into their development plans, provide valuable insights. The findings suggest that comprehensive policy frameworks, investment in education and innovation, and enhanced access to financial resources are essential for overcoming current challenges. Ultimately, the research offers recommendations for strengthening policies that support a sustainable creative economy, ensuring long-term socio-economic benefits. Keywords: Creative economy, sustainable development, policy integration, government role